Ferroptosis and Its Role in Epilepsy - Cai, Yuxiang; Yang, Zhiquan (Frontiers in Cellular Neuroscience, 2021)
Epilepsy is one of the most common symptoms of many neurological disorders. The typical excessive, synchronous and aberrant firing of neurons originating from different cerebral areas cause spontaneous recurrent epileptic seizures. Prolonged epilepsy can lead to neuronal damage and cell death. The mechanisms underlying epileptic pathogenesis and neuronal death remain unclear. Ferroptosis is a newly defined form of regulated cell death that is characterized by the overload of intracellular iron ions, leading to the accumulation of lethal lipid-based reactive oxygen species (ROS). To date, studies have mainly focused on its role in tumors and various neurological disorders, including epilepsy. Current research shows that inhibition of ferroptosis is likely to be an effective therapeutic approach for epilepsy. In this review, we outline the pathogenesis of ferroptosis, regulatory mechanisms of ferroptosis, related regulatory molecules, and their effects on epilepsy, providing a new direction for discovering new therapeutic targets in epilepsy.